Industrial Policy and Development 2009
DOI: 10.1093/acprof:oso/9780199235261.003.0019
|View full text |Cite
|
Sign up to set email alerts
|

19 Intellectual Property and Industrial Development: A Critical Assessment

Abstract: This chapter offers a sort of roadmap for the analysis of the relationship between intellectual property right protection and industrial development. The general point is that all successful catching-up episodes occurred under condition of weak IPR regimes, allowing easier knowledge acquisition and imitation. Conversely, strong IPR regimes are strongly promoted by countries on the innovation frontier. Nowadays, the latter, and in particular the US, strategically use IP protection as a mechanism to protect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…But this success was only one moment in broader transformations that would simultaneously heighten contests over GR and bring them head to head with concomitant contests over IP rules over the next decade: ten years later, the CBD had been agreed and TRIPS followed. Neither mentioned the 'common heritage' principle and both confirmed that GRs were to be regulated as commodities (Cimoli, et. al 2008).…”
Section: Cbdmentioning
confidence: 99%
“…But this success was only one moment in broader transformations that would simultaneously heighten contests over GR and bring them head to head with concomitant contests over IP rules over the next decade: ten years later, the CBD had been agreed and TRIPS followed. Neither mentioned the 'common heritage' principle and both confirmed that GRs were to be regulated as commodities (Cimoli, et. al 2008).…”
Section: Cbdmentioning
confidence: 99%
“…Notably, the already substantial federal research and development levels were more or less maintained through the floating of massive issues of Treasury bonds and other forms of government debt during the 1980s. The aim of this spending (which was achieved) was both geopolitical and a matter of strengthening of the United States' technological base and competitiveness vis-à-vis other countries (Cimoli, Coriat, and Primi, 2008). But Brazil and other countries affected by the debt crisis not only could not borrow to support research and development but also had to channel increasingly substantial domestic resources into servicing the existing debt.…”
Section: The Marginalization-modernization Nexus and Technological Progressmentioning
confidence: 99%
“…The most radical means through which this was achieved was the 1994 World Trade Organization's Agreement on Trade-related Aspects of Intellectual Property Rights (TRIPS)-initiated in the mid-1980s at the insistence of the United States-that mandated high and binding intellectual property protection standards in all its signatories regardless of the different social, economic, and cultural conditions prevailing in them. Being an extension of developed countries' industrial policies, TRIPS was a means to protect their competitive advantage in high-tech sectors, including pharmaceuticals, in the emergent global knowledge economy (Cimoli, Coriat, and Primi, 2008;May, 2000). After signing on to the TRIPS Agreement in the mid-1990s, Brazil saw its already weakly articulated technological learning networks disintegrate further precisely at a time when developed countries were aggressively protecting the assets of their high-tech sectors.…”
Section: The Marginalization-modernization Nexus and Technological Progressmentioning
confidence: 99%
“…Trade‐related aspects of intellectual property rights (TRIPS) represent the biggest change in global IP regimes at the international level of the last two decades (Basheer ; Cimoli et al . ). TRIPS require that WTO member nations enact and enforce laws on copyrights, trademarks and patents to protect intellectual property.…”
Section: Introductionmentioning
confidence: 97%
“…Arguments against the reinforcement of IPRs emphasise the possibility of important welfare losses due to market power pricing, the costs of closing down infringing activities, higher imitation costs and other risks related to patenting indigenous knowledge, enforcement problems and the adverse impact on the trajectory of technological learning and catching up, as well as the mismatch between IP policies, innovation policy and industrial policy (Cimoli and Primi ; Cimoli et al . ).…”
Section: Introductionmentioning
confidence: 97%